Instant messaging application for the care of people living with HIV/aids - Ivana Cristina Vieira de Lima; Marli Teresinha Gimeniz Galvão; Samyla Citó Pedrosa; Odaleia Oliveira Farias; Camila Aparecida Costa Silva; Gilmara Holanda da Cunha
ABSTRACT Objective: To assess a specific instant messaging application as a tool of care for people living with HIV/aids, based on analysis of the interactions between nurse and patients. Method: Descriptive, quantitative study with 102 patients from two outpatient infectious disease clinics of Fortaleza, Ceará. During four months, participants received a message every 15 days, totaling eight messages, regarding: adherence to antiretroviral therapy; physical activity; social support; self-esteem; anxiety/depression; eating habits; alcohol and drugs; and sexuality. Results: There were 816 interactions, especially for dialogs about performing physical activity (27.87%), sharing of signs and symptoms (18.03%), report of engagement with treatment (9.84%) and requests of information on the intake of medicine (9.84%). Most participants showed satisfaction with the follow-up, with willingness to continue receiving messages (90.58%). Conclusion: The use of this application is a viable strategy to improve care for people with HIV by promoting instant communication.